Mutation status of K-ras, p53 and allelic losses at 9p and 18q are not prognostic markers in patients with pancreatic cancer - Salek, Cyril; Minarikova, Petra; Benesova, Lucie; Nosek, Vladimir; Strnad, Robin; Zavoral, Miroslav; Minarik, Marek (Anticancer research, 2009)
BACKGROUND: K-ras mutations and allelic losses of tumor suppressors p16 and DPC4 are perceived as potential markers for screening of pancreatic malignancy. In this study, molecular data is compared with survival statistics of the patients and whether they correlate with patients' prognosis is questioned. PATIENTS AND METHODS: Fifty three consecutive patients with advanced pancreatic cancer (stage III and IV) who underwent EUS-guided fine needle aspiration (FNA) were enrolled into the study (28 males, 25 females, 63+/-10.5 years). Samples were evaluated on-site for presence of malignant cells. DNA was extracted from Giemsa stained smears using laser microdissection, and mutation status of K-ras and p53 was tested by cycling-gradient capillary electrophoresis (CGCE). In addition, allelic losses of tumor suppressor genes p16 (INK4, CDKN2A) and DPC4 (MADH4, SMAD4) were detected by monitoring the loss of heterozygosity (LOH) at 9p and 18q loci. Molecular data were compared with survival statistics using Kaplan-Meier method. RESULTS: The median survival in K-ras positive group was 7.0+/-2.4 months (95% CI 2.3-11.7) and in K-ras negative group was 10.0+/-0.6 months (95% CI 8.7-11.3). The median survival in p53 positive group was 10.0+/-2.2 months (95% CI 5.6-14.4) and in p53 negative group was 6.0+/-2.5 months (95% CI 1.1-10.9). The median survival in LOH 9p positive group was 9.0+/-5.1 months (95% CI 0-18.9), in LOH 9p negatives was 10.0+/-5.0 months (95% CI 0.2-19.8). The median survival in LOH 18q positive group was 10.0+/-4.2 months (95% CI 1.8-18.2) and in LOH 18q negative group was 3.0+/-1.3 months (95% CI 0.5-5.5). After the adjustment for age using Cox proportional hazards model, none of the evaluated molecular markers was shown to be an independent prognostic marker for survival of patients with pancreatic cancer. CONCLUSION: None of the studied molecular markers was identified as an independent factor determining survival prognosis.
Keywords: mutace; chromozomální delece; lidské chromozomy, pár 9; Genes, p53; geny ras; Pancreatic Neoplasms; Chromosomes, Human, Pair 18; geny p53; lidé; Survival Analysis; nádory slinivky břišní; Mutation; Chromosomes, Human, Pair 9; Genes, ras; prognóza; lidské chromozomy, pár 18; Chromosome Deletion; alely; Prognosis; analýza přežití; Alleles; Humans